Pemberdayaan Pembudidaya Ikan dan Udang Tambak, Desa Kendalkemlagi, Kecamatan Karanggeneng, Kabupaten Lamongan, Propinsi Jawa Timur [Empowerement For Fish and Prawn Farmers In Pond At Kendalkemlagi Village, Karanggeneng District, Lamongan Regency, East Java Province ] - Muhammad Arief; Akhmad Taufiq Mukti; Sudarno Sudarno (Faculty of Fisheries and Marine Universitas Airlangga, 2011)
Abstract The aim of this IbM program was empowerement for fish and prawn farmers through good conducting and correctness management of fish and prawn cultures in pond. Activity method were discussion and training on management of fish and prawn culture in pond.. Result of this IbM program were improve knowledge and skill of fish and prawn farmers to manage well and correctness of fish and prawn cultures in pond. This program can used to effort increase production yield of fish and prawn cultures in pond.